A66 CHARACTERIZATION OF PERIPHERAL BLOOD AND LAMINA PROPRIA LYMPHOCYTES IN CROHN'S DISEASE. (1st March 2018) - Power, N; Jeyalingam, T; Filice, M; Smith, M; Silverberg, M S; Steinhart, A; Nguyen, G C; Zezos, P; Croitoru, K
Abstract: Background: Stimulation of the intestinal immune system is an important contributor to the pathogenesis of Crohn's disease. This includes possible changes in regulatory T cells (Tregs), mucosal-associated invariant T cells (MAIT), and helper T cells (Th cells). Aims: We aimed to characterize and compare T-lymphocyte subpopulations in the peripheral blood and intestinal lamina propria (LP) of healthy individuals and those with Crohn's disease (CD). Methods: Peripheral blood and LP biopsy specimens of the colon and ileum were collected from 33 patients with CD and 15 healthy controls (HC). Lymphocytes were isolated from the peripheral blood (PBL) and LP (LPL) and cell surface phenotype and intracellular cytokines were analyzed by flow cytometry. Specifically, we assessed markers of T cells (CD3+), Tregs (CD4+CD25+CD127-), MAIT cells (CD3+CD8+CD161high, Vα7.2+), and cells expressing α4β7 and αEβ7 integrins (Beta7+, CD103+). Cells were also stimulated with PMA and ionomycin for 4 hours at 37 o C and analyzed for cell surface phenotype and intracellular cytokine expression using Ab to IFNγ, TNFα, and IL17a. Results: When compared to HC, we found a decrease of MAIT and Tregs in the peripheral blood of CD patients (2.39% vs. 7.77%, P=0.0008; 2.8% vs. 5.9%, P<0.0001). In inflamed tissue of CD patients there was an increase in Tregs as compared to both HC and non-inflamed tissue of CD patients (3.17% vs. 1.87%, P= 0.0013; 3.17% vs. 1.86%, P=0.011). Interestingly, MAIT cell levels in LPL of HC were not significantly different from that of CD patients (3.73% vs 3.79%, P=0.6558). MAIT cells in the blood of CD patients produced more IL17a than MAIT cells from HC (5.72% vs. 2.68%, P=0.0242). Furthermore, we saw an increase in production of IL17a from α4β7 + and αEβ7 + cells in CD patients (15.3% vs. 11.83%, P=0.0401; 15.4% vs. 8.86%, P=0.0002) as well as an increase in LPL co-producing IFNγ and IL17a (5.81% vs. 3.66%, P=0.0003) and TNFα and IL17a (13.28% vs. 9.44%, P=0.0028), when compared to HC, regardless of disease activity. Conclusions: These data show that peripheral blood lymphocyte phenotype differs from gut LPL in HC and in CD. The increase in IFNγ-IL17a and TNFα-IL17a producing LPL suggest a disease state shift from Th1 cells to Th17 cells in CD. Taken together, these results suggest that intestinal Th17 cells can transition into Th1-like cells and pro-inflammatory stimuli may promote this conversion. It remains to be shown if therapy restores the balance of Th1 and Th17 cells. Together, these results provide insight into the immune profile of CD patients at baseline, prior to biologic treatment. Funding Agencies: AbbVie